The mediating effect of brain-derived neurotrophic factor levels on childhood trauma and psychiatric symptoms in patients with first-episode schizophrenia. (July 2022) - Wang, Leilei; Yin, Yi; Zhou, Yanfang; Huang, Junchao; Zhang, Ping; Chen, Song; Fan, Hongzhen; Cui, Yimin; Luo, Xingguang; Tan, Shuping; Wang, Zhiren; Li, Chiang-Shan R; et al.
Background: Previous studies have implicated childhood trauma and abnormal brain-derived neurotrophic factor in the pathogenesis of schizophrenia. Here, we explored whether brain-derived neurotrophic factor levels mediated the relationship between childhood trauma and psychopathological symptoms in patients with first-episode schizophrenia. Methods: Patients with first-episode schizophrenia ( n = 192) and healthy controls ( n = 136) were enrolled. Childhood traumatic experiences and psychopathology were assessed by Childhood Trauma Questionnaire and Positive and Negative Syndrome Scale, respectively. Enzyme-linked immunosorbent assay was used to quantify brain-derived neurotrophic factor levels. Results: The patients with first-episode schizophrenia experienced more severe childhood trauma and had lower serum brain-derived neurotrophic factor levels than healthy controls. Emotional abuse and Childhood Trauma Questionnaire total score showed positive correlation with Positive and Negative Syndrome Scale positive, general psychopathological subscore and total score. Emotional neglect showed positive correlation with Positive and Negative Syndrome Scale positive subscore. Physical neglect was positively associated with Positive and Negative Syndrome Scale negative subscore. Emotional neglect and Childhood Trauma Questionnaire total score were negatively correlated with serum brain-derived neurotrophic factor levels. The serum brain-derived neurotrophic factor levels mediated the relationship between both Childhood Trauma Questionnaire total score and Positive and Negative Syndrome Scale total score and negative symptoms in the patients. The brain-derived neurotrophic factor levels also mediated the relationship between emotional neglect and Positive and Negative Syndrome Scale total score in the patients. Conclusion: Childhood trauma might contribute to the clinical symptoms of schizophrenia by affecting brain-derived neurotrophic factor levels. Perhaps we can prevent schizophrenia by reducing childhood traumatic experiences.